2012
DOI: 10.1007/s00284-012-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes

Abstract: Members of group III histidine kinases from different filamentous fungi were previously shown to mediate osmoregulation and resistance to dicarboximide, phenylpyrrole and, aromatic hydrocarbon fungicides. In this study, we report the disruption of the gene encoding group III histidine kinase, AlHK1, in the economically important plant pathogen Alternaria longipes. The AlHK1 gene disruption had pleiotropic effects on this fungus. Besides the expected osmosensitivity and fungicides resistance, AlHK1 participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Adversely, no fitness penalty was found associated with dicarboximide resistance (and phenylpyrrole sensitivity) in field strains (Oshima et al, 2002, 2006). Notably, in some fungal species, no developmental defect besides osmosensitivity was found associated with phenylpyrrole resistance (Motoyama et al, 2005; Luo et al, 2012). …”
Section: Resistance To Phenylpyrrolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adversely, no fitness penalty was found associated with dicarboximide resistance (and phenylpyrrole sensitivity) in field strains (Oshima et al, 2002, 2006). Notably, in some fungal species, no developmental defect besides osmosensitivity was found associated with phenylpyrrole resistance (Motoyama et al, 2005; Luo et al, 2012). …”
Section: Resistance To Phenylpyrrolesmentioning
confidence: 99%
“…Field strains cross-resistant to phenylpyrroles and dicarboximides have been isolated from A. brassicicola, A. longipes , and A. alternata populations (Dry et al, 2004; Iacomi-Vasilescu et al, 2004; Avenot et al, 2005; Luo et al, 2012; Avenot and Michailides, 2015; Malandrakis et al, 2015). No significant developmental defects could be detected in the A. brassicicola resistant mutants and only moderate osmosensitivity (Avenot et al, 2005; Iacomi-Vasilescu et al, 2008).…”
Section: Resistance To Phenylpyrrolesmentioning
confidence: 99%
“…Resistance to PCNB has been documented in other ascomycete plant pathogens, including Botrytis cinerea and Sclerotinia sclerotiorum, as well as in Alternaria sp. and Magnaporthe oryzae (Steel & Nair, 1993;Bradley et al, 2006;Luo et al, 2012). Recently, Luo et al (2012) demonstrated that an osmosensitive signal transduction pathway present in many of these fungi governs resistance to both PCNB and dicarboximides.…”
Section: Discussionmentioning
confidence: 99%
“…and Magnaporthe oryzae (Steel & Nair, 1993;Bradley et al, 2006;Luo et al, 2012). Recently, Luo et al (2012) demonstrated that an osmosensitive signal transduction pathway present in many of these fungi governs resistance to both PCNB and dicarboximides. Whether the reduced sensitivity to PCNB in S. homoeocarpa isolate Heath1A in our in vitro assays correlates with practical resistance to this fungicide in the field or with crossresistance to dicarboximide fungicides is unknown, but additional studies with this isolate may be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The unique role for HK3 in sensing the fungicidal cue is similar to what has been learned from NikA, an HK3 homologue that was shown to play a major role in SakA (Hog1) phosphorylation in response to fludioxonil rather than to osmotic shock in A. fumigatus (Hagiwara et al ., ). However, the fungicide‐sensing role of HK3 is different from the reported roles of other Group III HKs (Os1/TcsC/Bos1/DrkA) in sensing both osmotic and fungicidal cues (Ochiai et al ., ; Liu et al ., ; McCormick et al ., ) or mediating the two hallmark phenotypes in several fungi, such as P. marneffei (Boyce et al ., ), Alternaria longipes (Luo et al ., ) and Fusarium oxysporum (Rispail and Di Pietro, ). Despite increased sensitivity to H 2 O 2 or menadione, the Δ hk3 cells triggered with or without H 2 O 2 showed the same signal of phosphorylated Hog1 as the cells of the control strains, suggesting no role for HK3 in sensing oxidative cue in B. bassiana .…”
Section: Discussionmentioning
confidence: 99%